Model dinamika sistem untuk pengembangan alternatif kebijakan pengelolaan hutan yang adil dan lestari - Purnomo, H. (2003)
System dynamic is an effort to understand complexity of social and eco-systems of forest. Through this system, a conscious learning on interactions between people and forest will take place in order to manage forest in more sustainable and equitable manners. A system dynamic modeling was carried out in area surrounding Lumut Mountain Forest, District of Pasir, and East Kalimantan. In the area, where legally was allocated to a logging company, live local people who depend on forest and rattan. The policy makers are trying to improve the well-being of local people without sacrifying the logging company. Aim of the study was to give policy options to policy makers and likely impacts of those options. The built model comprises biophysical, social, policy and impact main components. The model shows the the change of impact indicators, which are standing stock, community income, and concession revenue and government income, given any selected policy option.